Evaluation of azithromycin in systemic and toothpaste forms for the treatment of ciclosporin‐associated gingival overgrowth in dogs. Issue 3 (14th May 2013) - Rosenberg, Andrew; Rosenkrantz, Wayne; Griffin, Craig; Angus, John; Keys, Deborah
Abstract : Background: Gingival overgrowth is an adverse effect of ciclosporin therapy. Azithromycin (AZI) in capsule and toothpaste form is an effective treatment for ciclosporin‐associated gingival overgrowth (CsAGO) in humans. Hypothesis/Objectives: To evaluate AZI in a systemic and a toothpaste form for the treatment of CsAGO in dogs. The secondary objective was to determine which treatment is more effective. Animals: Thirty‐six client‐owned dogs with CsAGO. Methods: Dogs were randomly assigned to the following four groups: AZI capsule; AZI toothpaste; placebo capsule; and placebo toothpaste. Treatments were for 4 weeks, and measurements of gingival sulcus depth, tooth length and subjective global scores were taken at weeks 0, 2, 4 and 8. The AZI dose was 10 mg/kg daily, and brushing (8.5% AZI) was once daily. Results: There was a significant decrease in gingival sulcus depth for the AZI capsule group at week 8 and for the AZI toothpaste group at weeks 2, 4 and 8. The mean decrease in gingival sulcus depth was significantly greater in active versus placebo groups ( P = 0.0356). The tooth length and subjective global scores were not significantly different for any groups. Gastrointestinal adverse events occurred in all groups, but more frequently in the AZI capsule group. Conclusions and clinical importance: Azithromycin improved CsAGO in only one measured parameter, gingival sulcus depth. Only one dog in the AZI capsule group had complete resolution of CsAGO. Further studies are warranted. Azithromycin capsules were associated with the most gastrointestinal adverse effects.